2009
DOI: 10.2746/042516409x429419
|View full text |Cite
|
Sign up to set email alerts
|

Regional distribution of collagen and haemosiderin in the lungs of horses with exercise‐induced pulmonary haemorrhage

Abstract: The results support the hypothesis that repeated bouts of venous hypertension during strenuous exercise cause regional vein wall remodelling and collagen accumulation, venous occlusion and pulmonary capillary hypertension. Subjected to these high pressures, there is capillary stress failure, bleeding, haemosiderin accumulation and, subsequently, lung fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 24 publications
1
33
0
2
Order By: Relevance
“…Recently, other studies have demonstrated that downstream pulmonary veno‐occlusive remodelling occurs in EIPH‐positive horses . This condition, attributable to chronic hypertensive episodes within the lung, as described above, would increase the chances of EIPH reoccurrence and explain the worsening of EIPH with age.…”
Section: Lower Airway Disorders and Their Effects On Respiratory Funcmentioning
confidence: 86%
See 1 more Smart Citation
“…Recently, other studies have demonstrated that downstream pulmonary veno‐occlusive remodelling occurs in EIPH‐positive horses . This condition, attributable to chronic hypertensive episodes within the lung, as described above, would increase the chances of EIPH reoccurrence and explain the worsening of EIPH with age.…”
Section: Lower Airway Disorders and Their Effects On Respiratory Funcmentioning
confidence: 86%
“…Recent advances in technology have enabled the development of portable endoscopes that may be used during ridden or driven exercise in the field (Fig ) . The advantages of overground endoscopy include the ability to exercise the horse in its natural environment while being ridden and without the need for referral to a specialist centre with a treadmill.…”
Section: Upper Airway Disorders and Their Effects On Respiratory Funcmentioning
confidence: 99%
“…The diagnosis is made by finding blood upon tracheoscopy104 or by detecting hemosiderin in alveolar macrophages 105. Hemorrhage occurs almost exclusively in the caudo‐dorsal lung areas and is associated with macrophagic bronchiolitis and fibrosis 106. The potential association between IAD and EIPH is controversial.…”
Section: Differential Diagnosesmentioning
confidence: 99%
“…Multiple occurrences of EIPH result in angiogenesis and fibrosis of the lung that ultimately leads to reduced elasticity of the lung and decreased capacity for oxygen uptake (McKane and Slocombe 2002; Williams et al . 2008; Derksen et al . 2009).…”
Section: Introductionmentioning
confidence: 99%